Increased circulating macrophage migration inhibitory factor levels are associated with coronary artery disease (Clinics, 2015)
BACKGROUND: To evaluate the macrophage migration inhibitory factor and E-selectin levels in patients with acute coronary syndrome. MATERIALS/METHODS: We examined the plasma migration inhibitory factor and E-selectin levels in 87 patients who presented with chest pain at our hospital. The patients were classified into two groups according to their cardiac status. Sixty-five patients had acute myocardial infarction, and 22 patients had non-cardiac chest pain (non-coronary disease). We designated the latter group of patients as the control group. The patients who presented with acute myocardial infarction were further divided into two subgroups: ST-elevated myocardial infarction (n = 30) and non-ST elevated myocardial infarction (n = 35). RESULTS: We found higher plasma migration inhibitory factor levels in both acute myocardial infarction subgroups than in the control group. However, the E-selectin levels were similar between the acute myocardial infarction and control patients. In addition, we did not find a significant difference in the plasma migration inhibitory factor levels between the ST elevated myocardial infarction and NST-elevated myocardial infarction subgroups. DISCUSSION: The circulating concentrations of migration inhibitory factor were significantly increased in acute myocardial infarction patients, whereas the soluble E-selectin levels were similar between acute myocardial infarction patients and control subjects. Our results suggest that migration inhibitory factor may play a role in the atherosclerotic process.